AB1331-HPR ACTIVE DISEASE ACTIVITY IN ANKYLOSIS SPONDYLITIS: WORSE OUTCOMES AND POORER HR-QOL. (2nd June 2020) - Zhou, W.; He, M.; Zhao, R.; Dong, C.; Gu, Z.
Abstract : Background: Ankylosing spondylitis (AS) is a chronic inflammatory disease that mainly affects the sacroiliac joints and the spine, resulting in decline in quality of life[1, 2]. Poor QoL is significantly related to high disease activity[3]. However, there is no systematic report on which prognosis indicators are affected by disease activity in AS patients. Objectives: This study aimed to evaluate the patient-reported outcome measures and health-related quality of life (HR-QoL) in AS patients defined on the basis of the Bath Spondylitis Ankylosing Disease Activity Index (BASDAI). Methods: 204 AS patients were involved in this study. A serious of questionnaires were used to overall assess AS patients, which include: Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Bath Ankylosing Spondylitis Metrology Index (BASMI), Bath Ankylosing Spondylitis Functional Index (BASFI), the 10 cm Visual Analog Scale (VAS), the Self-Rating Anxiety Scale (SAS), the Self-Rating Depression Scale (SDS), the Pittsburgh Sleep Quality Index (PSQI), the Health Assessment Questionnaire-Disability Index (HAQ-DI), the Fatigue Severity Scale(FSS) and the Short Form 36 Health Survey (SF-36). Independent samples t-test, Mann–Whitney U-test, Chi-square analysis and Pearson /Spearman correlation were used to analyze the data. Results: The results demonstrated 31.4% AS patients were in active disease activity stage. Active AS patients were older, unemployed, and had less exercise therapy than stable AS patients. Besides, AS patients with active disease activity presented more severe pain( P <0.001), poor physical function( P <0.001) and spinal mobility( P <0.001). They were more anxious( P <0.001), depressed( P <0.001) and had more sleep disturbance( P =0.001). Compared with active AS patients, stable AS patients had more leukocytes( P =0.040), lymphocytes( P =0.002), erythrocytes( P =0.001) and hemoglobin( P <0.001). Active disease activity had a significant impact on all dimensions of quality of life in AS patients( P <0.001). Conclusion: These findings suggested that medical personnel should pay more attention to active AS patients and make effective interventions to improve quality of life. References: [1]Exarchou S, Lindstrom U, Askling J, Eriksson JK, Forsblad-d'Elia H, Neovius M, Turesson C, Kristensen LE, Jacobsson LT (2015) The prevalence of clinically diagnosed ankylosing spondylitis and its clinical manifestations: a nationwide register study. Arthritis research & therapy 17:118. doi:10.1186/s13075-015-0627-0 [2]Qian Q, Xu X, He H, Ji H, Zhang H, Ding Y, Dai SM, Zou Y, Zhu Q, Yang C, Ye S, Jiang L, Tang JP, Tong Q, He D, Zhao D, Li Y, Ma Y, Zhou J, Yuan Z, Zhang J, Jin L, Zhou X, Reveille JD, Zou H, Wang J (2017) Clinical patterns and characteristics of ankylosing spondylitis in China. Clinical rheumatology 36 (7):1561-1568. doi:10.1007/s10067-017-3660-3 [3]Huang JC, Qian BP, Qiu Y, Wang B, Yu Y, Zhu ZZ, Hu J, Qu Z (2017) Quality of life and correlation with clinical and radiographic variables in patients with ankylosing spondylitis: a retrospective case series study. BMC musculoskeletal disorders 18 (1):352. doi:10.1186/s12891-017-1711-1 Acknowledgments: Thanks to all the authors for their efforts and thanks to all members of the Department of Rheumatology of Affiliated Hospital of Nantong University for their helpfulness in the acquisition of data. Disclosure of Interests: None declared